Some peculiarities of self-appraisal of personality by future teachers - Jacikevičius, A. (Psichologija, 1984)
Self-attitude was investigated after the methods of M. Kuhn by the students of the Klaipėda department of the State Conservatoire of the Lithuanian SSR. Self-appraisal of the peculiarities of personality was compared with group appraisal. The attitude of the students towards the appraisal of their personality given by their parents, their friends and teachers was looked into. The investigation has shown some trends of overestimation of negative characteristics of personality, inadequacy of subjective and objective appraisal of personality of the future teachers. The results showing some peculiarities of self-consciousness of the students could be used for test methods.
Keywords: self appraisal; self esteem; self evaluation; future teachers